2012
DOI: 10.1128/aem.07360-11
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time PCR Detection of Phaeomoniella chlamydospora and Phaeoacremonium aleophilum

Abstract: ABSTRACTPhaeomoniella chlamydosporaandPhaeoacremonium aleophilumare the two main fungal causal agents of Petri disease and esca. Both diseases cause significant economic losses to viticulturalists. Since no curative control measures are known, proactive defensive measures must be taken. An important aspect of current research is the develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Recently, qPCR methods with great potential for use in pathogen‐free certification schemes have been set up for Phaeomoniella chlamydospora and Phaeoacremonium aleophilum, the main causal agents of Petri disease and esca in grapevine wood (Martín et al. ) and for quarantine pathogens such as Plasmopara haistedii (Ioos et al. ) and Ceratocystis platani (Pilotti et al.…”
Section: Detection Of Phytopathogenic Fungi and Oomycetes In Host Tismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, qPCR methods with great potential for use in pathogen‐free certification schemes have been set up for Phaeomoniella chlamydospora and Phaeoacremonium aleophilum, the main causal agents of Petri disease and esca in grapevine wood (Martín et al. ) and for quarantine pathogens such as Plasmopara haistedii (Ioos et al. ) and Ceratocystis platani (Pilotti et al.…”
Section: Detection Of Phytopathogenic Fungi and Oomycetes In Host Tismentioning
confidence: 99%
“…Given the high importance of an accurate detection of quarantine pathogens and the risk of false positive/negative results, a statistical procedure has been proposed to determine the cycle cut-off and the corresponding limit of detection in qPCR (Chandelier et al 2010). Recently, qPCR methods with great potential for use in pathogen-free certification schemes have been set up for Phaeomoniella chlamydospora and Phaeoacremonium aleophilum, the main causal agents of Petri disease and esca in grapevine wood (Mart ın et al 2012) and for quarantine pathogens such as Plasmopara haistedii (Ioos et al 2012) and Ceratocystis platani (Pilotti et al 2012).…”
Section: Detection Of Phytopathogenic Fungi and Oomycetes In Host Tismentioning
confidence: 99%
“…The nested qPCR approach presented in this study has enabled the detection of up to 1 fg/μl of target DNA. Other studies have found variable limits of detection (from 1 to 250 fg) of Pch in water, wood, callusing medium and nursery soil using diverse techniques such as nested PCR, TaqMan® qPCR and multiplex Plexor™ qPCR (Martín, Cobos, Martín, & López‐Enríquez, ; Pouzoulet et al, ; Retief et al, ). In this study, the specificity of Pch quantification in vineyard soils was confirmed by way of melting curve analysis, in accordance with (Pouzoulet et al, ) who proved that this technique is essential to unequivocal detection of Pch DNA by distinguishing between specific and unspecific signals.…”
Section: Discussionmentioning
confidence: 99%
“…UniFrac compares communities by integrating the phylogenetic (P) test and the F ST test (88). The F ST test assesses genetic diversity and indicates whether less genetic diversity is present within each community when compared to both communities combined.…”
Section: Comparing Between Communitiesmentioning
confidence: 99%